THE ILLUSION OF WILLY LOMAN’S IN ARTHUR MILLER’S DEATH OF A SALESMAN - sumarsono, irwan (Dinamika : Jurnal Sastra dan Budaya, 2019)
This study discusses the illusion and explains the conditions that lead the main character, Willy Loman to be in illusion. The analysis will be focused on the characterization of Willy Loman, his marriage with Linda Loman, his relationship with his sons, Biff and Happy. The analysis also focuses on the illusion of Willy Loman by discovering why he cannot face the reality and   what the effects to his life. To analyze these problems, the writer uses the psychological approach since psychology and literary works cannot be separated.